PENGARUH KEPRIBADIAN, PENGETAHUAN KEWIRAUSAHAAN, KREATIVITAS DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA - Marselina Murniati; Sulistyo Sulistyo; Udik Yudiono (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
The purpose of this study was to determine the Effect of Personality, Entrepreneurship Knowledge, Creativity and Family Environment on Mint Entrepreneurship Student Economics Education Universitas Kanjuruhan Malang. This type of research uses ex post facto, using multiple linear regression analysis. The study was conducted at Universitas Kanjuruhan Malang Faculty of Economics and Business Economics Education Students. The population in this study were students of economic education in 2016 and 2017 totaling 65 students with sampling techniques using saturated sample techniques. Data collection uses questionnaires and documentation. Based on the calculation results it is known that: (1) there is an influence between Personality, Entrepreneurship Knowledge, Creativity and Family Environment on Entrepreneurial Interest in Economic Education Students in Universitas Kanjuruhan Malang (2) there is an influence between Personality on Entrepreneurial Interest in Economic Education Students in Universitas Kanjuruhan Malang. (3) there is an influence between Entrepreneurship Knowledge on Entrepreneurial Interest in Economic Education Students in Universitas Kanjuruhan Malang. (4) there is an influence between Creativity on Entrepreneurial Interest in Economic Education Students in Universitas Kanjuruhan Malang. (5) there is an influence between the Family Environment on Student Entrepreneurial Interest in Economic Education, Universitas Kanjuruhan Malang.